Muscle-derived extracellular vesicles mediate crosstalk between skeletal muscle and other organs - Jia, Jiajie; Wang, Lu; Zhou, Yue; Zhang, Peng; Chen, Xiaoping (Frontiers in Physiology, 2025)
Skeletal muscle (SKM) has crucial roles in locomotor activity and posture within the body and also functions have been recognized as an actively secretory organ. Numerous bioactive molecules are secreted by SKM and transported by extracellular vesicles (EVs), a novel class of mediators of communication between cells and organs that contain various types of cargo molecules including lipids, proteins and nucleic acids. SKM-derived EVs (SKM-EVs) are intercellular communicators with significant roles in the crosstalk between SKM and other organs. In this review, we briefly describe the biological characteristics, composition, and uptake mechanisms of EVs, particularly exosomes, comprehensively summarize the regulatory effects of SKM-EVs on the function of, which include myogenesis, muscle repair and regeneration, as well as metabolic regulation. Furthermore, we explore the impact of SKM- EVs on various organs including bone, the cardiovascular system, adipose tissue, and nervous system. As emerging evidence suggests that SKM-EVs are involved in the development and regulation of type 2 diabetes (T2D), systemic inflammation, and other chronic diseases, we also highlight the potential of SKM-EVs as therapeutic targets and diagnostic biomarkers, emphasizing the need for further research to elucidate the complex mechanisms underlying intercellular communication in physiological and pathological contexts.